Controlling Vaporization Time as Effective Parameter on Purified Vertically Aligned Carbon Nanotubes Based on CVD Method - Yousefi, A.T.; Bagheri, Samira; Kadri, Nahrizul Adib; Mahmood, Mohamad Rusop; Ikeda, Shoichiro (Taylor & Francis, 2015)
The unique properties of Carbon nanotubes (CNTs) were determined from 15 years' worth of scientific investigation in the context of multiple applications. Here, we report the effect of time dependent temperature on camphor oil within 500-1150°C of different vaporization times. According to the results, the CNTs growth rate was increased abruptly by increasing vaporization time. This process was conducted in similar conditions by optimizing the temperature to up to 900°C. FESEM images indicate that the highest catalytic activity was achieved at 180°C and 800°C of first and second furnace, respectively, directing the experiment in growing purified CNT to up to 111 μm in length during the 30 minutes reaction time. It was also gleaned from the results that at the lower vaporization time and temperature, the catalyst-support interaction is not completed to allow the metal particles to partake in the deposition process, but in the optimized vaporization process, MWCNTs can be selectively grown as a function of CVD time. The optimum vaporization time was determined to be 30 minutes, which based on the Raman shift results; the grown CNTs exhibited high purity and crystallinity, as well as a desired aspect ratio.